Hubungan Pemberian ASI dengan Tumbuh Kembang Bayi Umur 6 Bulan di Puskesmas Nanggalo - Dian Insana Fitri; Eva Chundrayetti; Rima Semiarty (Fakultas Kedokteran, Universitas Andalas, 2014)
AbstrakBayi mengalami proses tumbuh kembang yang dipengaruhi oleh beberapa faktor, salah satunya adalah gizi. Unsur gizi pada bayi dapat dipenuhi dengan pemberian ASI, bahkan sampai umur 6 bulan sesuai rekomendasi WHO tahun 2001 diberikan ASI eksklusif. Namun, angka pencapaian ASI eksklusif di Indonesia masih rendah yaitu 61,5% dan puskesmas Nanggalo 65%. Tujuan penelitian untuk mengetahui hubungan pemberian ASI dengan tumbuh kembang bayi umur 6 bulan di Puskesmas Nanggalo. Penelitian ini merupakan studi analitik dengan desain cross sectional. Pertumbuhan dinilai melalui status gizi dan perkembangan melalui Tes Denver II, dengan jumlah sampel 50 bayi. Analisis statistik yang digunakan adalah uji chi square dengan derajat kemaknaan 0,05.Hasil penelitian menunjukkan pemberian ASI eksklusif masih rendah (30%) dibandingkan ASI non eksklusif (70%). Bayi ASI eksklusif berpeluang mengalami pertumbuhan normal 1,62 kali lebih besar dibandingkan bayi ASI non eksklusif (nilai OR = 1,62) dan perkembangan sesuai umur 5,474 kali lebih besar dibandingkan bayi ASI non eksklusif. Namun, pada pertumbuhan diperoleh nilai p = 0,696 dan nilai p perkembangan= 0,062 sehingga hubungan pemberian ASI terhadap tumbuh kembangan tidak signifikan. Penelitian ini memperlihatkan bahwa tidak terdapat hubungan antara pemberian ASI dengan tumbuh kembang bayi umur 6 bulan di Puskesmas Nanggalo Kota Padang.Kata kunci: Bayi umur 6 bulan, Pemberian ASI, Tumbuh KembangAbstractThe infant has a process of growth and development that is affected by several factors, one of them is nutrition. The element of nutrition for infant can be fulfilled by breast feeding, WHO (2011) recommends the infant should be given the exclusive breast feeding until it reaches 6 months old. However, the achievement number of exclusive breast feeding in Indonesia is still low (61.5%) and in the Nanggalo Community Health Center (65%). The aim of this research is to know the relationship between the breast feeding with the growth and development of 6 months old infants in the Nanggalo Community Health Center.This research was analytical study using cross sectional design, by assessing the nutritional status of infants through growth and development that assessed with tests of the Denver II, sample size 50 infants which were given the breast feeding. The statistical analysis test that used was chi square with the degree of significancy 0.05.The results shows that the exclusive breast feeding is still low (30%) compared to the non-exclusive breast feeding (70%). The infants who get the exclusive breast feeding have chance to experience the normal growth 1,62 times more than the non-exclusive breast feeding infants (OR value = 1,62) and the development which is appropriated to ages 5,474 times more than the non-exclusive breast feeding infants. But, p value of growth 0,696 and p value of development 0,062, so there is no significant relationship between the breast feeding with growth and development.This research shows that there is no relationship between the breast feeding with the growth and development of 6 months old infants in the Nanggalo Community Health Center.Keywords:6 months old infants, Breast feeding, Growth and development